2016
DOI: 10.3201/eid2208.151885
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic Evidence for 2 Genetically Distinct ZoonoticPlasmodium knowlesiParasites, Malaysia

Abstract: Sequence analyses of genes derived from human and macaque samples led to the proposal that 2 distinct types exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 28 publications
7
43
2
Order By: Relevance
“…The Philippine, MR4 and the Hackeri Strains formed a separate group along with Malaysian Borneo isolates. The distinct sub-populations observed in other invasion gene of P. knowlesi like MSP1P, DBPRII, NBPXA and TRAP was not observed in MSP7D [23, 2527, 31, 49]. (Fig.5).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The Philippine, MR4 and the Hackeri Strains formed a separate group along with Malaysian Borneo isolates. The distinct sub-populations observed in other invasion gene of P. knowlesi like MSP1P, DBPRII, NBPXA and TRAP was not observed in MSP7D [23, 2527, 31, 49]. (Fig.5).…”
Section: Resultsmentioning
confidence: 90%
“…P. knowlesi has a 24-hour erythrocytic cycle thus rapid increase in parasitaemia has been associated with the development of severe malaria and also a common cause for severe and fatal malaria in Malaysian Borneo [3, 2022]. Studies on mitochondrial and ssrRNA genes in P. knowlesi from patients and wild macaques identified two distinct sub-populations which clustered geographically to Peninsular Malaysia and Malaysian Borneo [23]. Additionally, genetic and genomic studies from Malaysia identified 3 distinct sub-populations; two originating from Sarawak and one from Peninsular Malaysia [2427] thereby highlighting the complexity of infections in humans and the challenges for control as well as vaccine design.…”
Section: Introductionmentioning
confidence: 99%
“…Human infections in Malaysian Borneo, the portion of Malaysia on the island of Borneo, have divergent genetic subpopulations that are seen in the different macaque species locally, indicating that 2 independent zoonoses may be occurring sympatrically ( 9 ). Noticeable geographic differentiation of parasites between Malaysian Borneo and peninsular Malaysia was also evident in microsatellite analysis; separate studies have revealed divergence between the 2 regions at unlinked genes encoding the normocyte binding protein ( 10 12 ) and the Duffy binding protein ( 13 , 14 ), as well as the 18S rRNA and mitochondrial cytochrome oxidase subunit 1 ( 15 ). Whole-genome sequencing has confirmed the presence of 2 divergent subpopulations of P. knowlesi in Malaysian Borneo and revealed a third divergent cluster of laboratory isolates maintained in laboratories since the 1960s; most of these were recorded to have originated from peninsular Malaysia ( 16 ).…”
mentioning
confidence: 93%
“…(C) Inhibition of P cynomolgi countries. [19][20][21] By contrast, to date, only 1 case of zoonotic P cynomolgi has been reported recently from Malaysia, 22 and it came to light solely through careful molecular analysis. Three interrelated factors might account for the disparity in the observed prevalence of zoonotic infections for these 2 species that have similar high prevalence in their natural hosts.…”
Section: Introductionmentioning
confidence: 99%